KORELASI ANTARA SIKAP DISIPLIN DAN AKTIVITAS SISWA DENGAN HASIL BELAJAR TEMATIK KELAS V - Ratna Juita; Tahmid Sabri; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the correlation between disciplinary attitudes and student activities with the thematic learning outcomes of class V at SDN Cluster I South Pontianak. The research used is correlation study. The sample in the study were 60 students who were determined by purposive sampling technique, namely class V SDN 14 South Pontianak, amounting to 24 students and class V SDN 12 South Pontianak, totaling 36 students. The results showed the statistical calculations using the product moment correlation formula that is the discipline attitude towards the thematic learning outcomes obtained rcount of 0.642 and student activities towards thematic learning outcomes obtained rcount of 0.342. As well as a disciplined attitude towards student activities, a rcount of 0.057 was obtained. For the attitude of discipline and student activities towards thematic learning outcomes using the multiple correlation formula obtained ??12 of 0.711 with Fcount of 29.14 and Ftable ? = 5% of 3.17 which means Fcount (29.14)> Ftable (3,17), then Ha is accepted. So, it can be concluded that there is a relationship between the attitude of discipline and student activities with the thematic learning outcomes of class V at SDN Cluster I South Pontianak.Keywords: Activity, Discipline, Outcomes